Throughfall, stemflow, and interception characteristics of coniferous forest ecosystems in the western black sea region of Turkey (Daday example) - Aydın, Miraç; Güneş Şen, Senem; Celik, Seval (Springer Science and Business Media LLC, 2018)
This study aims to identify precipitation, throughfall, stemflow, precipitation, and interception processes in pure black pine, pure Scots pine, and mixed black pine-Scots pine forest ecosystems and present the precipitation partitioning according to different stand types. Throughfall and stemflow measurements were performed using five standard precipitation gauges in a pilot area established to represent pure black pine, pure Scots pine, and mixed black pine-Scots pine stands in the Bezirgan Basin. The total precipitation was measured in an open field close to the study area. Throughfall values were calculated as the percentage of precipitation measured in an open field. According to the results of the study, the throughfall values were 69.8% in black pine, 73.9% in Scots pine, and 77.7% in the mixed black pine-Scots pine stands; the stemflow values were 2.6% in black pine, 5.9% in Scots pine, and 3.1% in the mixed black pine-Scots pine stands; the amounts of precipitation reaching the forest floor were 72.3% in black pine, 79.8% in Scots pine, and 80.7% in the mixed black pine-Scots pine stands; and the interception values were found to be 27.7% in black pine, 20.2% in Scots pine, and 19.2% in the mixed black pine-Scots pine stands.
Keywords: Turkey; Rain; Pinus sylvestris; Forests; Pinus; Trees; Tracheophyta; Black Sea; Ecosystem; Environmental Monitoring; 2. Zero hunger; 15. Life on land